2022
DOI: 10.3390/jcm11237237
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cryopreservation Technique for Xenogeneic Kidney Grafts: Evaluation Using a Mouse Model

Abstract: To align the xeno-metanephros and renal progenitor cell timing for transplantation treatments, cryopreservation techniques and an efficient transportation of regenerated renal products such as xeno-metanephroi and renal progenitor cells should be established. Therefore, we propose a novel method of xenogeneic regenerative medicine for patients with chronic kidney disease by grafting porcine fetal kidneys injected with human renal progenitor cells. To develop a useful cryopreserve system of porcine fetal kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…MNBs were cryopreserved via vitrification as previously reported [ 9 , 10 , 12 ]. First, the MNBs were equilibrated in base medium (MEM α supplemented with 20% fetal bovine serum (FBS; SH30070.03, HyClone Laboratories, Inc., Logan, UT, USA) and 1% antibiotic–antimycotic solution [15,240,062; Thermo Fisher Scientific, Waltham, MA, USA]) with 7.5% ethylene glycol (EG; 055-00996; Wako, Osaka, Japan) and 7.5% dimethyl sulfoxide (DMSO; 317275-100ML; Millipore, Burlington, MA, USA) on ice for 15 min and soaked in base medium with 15% EG and 15% DMSO on ice for an additional 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MNBs were cryopreserved via vitrification as previously reported [ 9 , 10 , 12 ]. First, the MNBs were equilibrated in base medium (MEM α supplemented with 20% fetal bovine serum (FBS; SH30070.03, HyClone Laboratories, Inc., Logan, UT, USA) and 1% antibiotic–antimycotic solution [15,240,062; Thermo Fisher Scientific, Waltham, MA, USA]) with 7.5% ethylene glycol (EG; 055-00996; Wako, Osaka, Japan) and 7.5% dimethyl sulfoxide (DMSO; 317275-100ML; Millipore, Burlington, MA, USA) on ice for 15 min and soaked in base medium with 15% EG and 15% DMSO on ice for an additional 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…For clinical application, properly preserved, ready-to-use grafts may be useful because the timing of transplantation must be adjusted according to the patient’s condition. We have previously demonstrated that cryopreserved fetal pig [ 9 ] and mouse [ 10 ] MNs differentiated well. However, an effective method to evaluate vitrified MNs has not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%